WATER DISPUTE: POLITICAL CONTEST AND INSTITUTIONAL MANAGEMENT IN THE CASE OF LOS CHORROS PARK, TACARES (2011-2018) - Valenciano Hernández, María Stephanie (2020)
This article consists in an analysis of the socio-environmental conflict that confronted two neighboring communities, but mainly one community and the State due to the water sources of Parque Los Chorros, between 2011 and 2018. This analysis is based on the model of the Spiral of Power and the Cycle of Political Demands proposed by Alpízar (2013), which seeks to understand what were the perceptions of the cause of the conflict, the demands and the articulation strategies of the political actors of the community, and later, the institutional processing that the Costa Rican State gave them. For this, is applied a qualitative research design that mainly identifies the cognitive frameworks with which the actors explain the conflict. Thus, it is possible to determine the existing inequalities between the communities and the State with the paternalistic practices with which manages water, as well as between the same community actors.